2016
DOI: 10.1002/ange.201603831
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective Cobalt(III)‐Catalyzed Three‐Component C−H Bond Addition Cascade

Abstract: A highly stereoselective three-component C(sp 2 )ÀH bond addition across alkene and polarized p-bonds is reported for which Co III catalysis was shown to be much more effective than Rh III . The reaction proceeds at ambient temperature with both aryl and alkyl enones employed as efficient coupling partners. Moreover, the reaction exhibits extremely broad scope with respect to the aldehyde input; electron rich and poor aromatic, alkenyl, and branched and unbranched alkyl aldehydes all couple in good yield and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…This approach provides an exciting opportunity for accessing complex structures from simple precursors particularly when one considers the number and diversity of possible permutations for combining C=C π-bond inputs such as alkenes, alkynes, dienes and allenes with polarized π-bond electrophiles such as carbonyls, imines, isocyanates, isocyanides and nitriles. 189,190 The initial reports reviewed here provide key proof-of-principle examples, which demonstrated that this approach can be achieved with high levels of regiocontrol, and when stereocenters are introduced, also diastereocontrol.…”
Section: Three-component Additions To C=c π-Bonds and Polarized πmentioning
confidence: 88%
See 1 more Smart Citation
“…This approach provides an exciting opportunity for accessing complex structures from simple precursors particularly when one considers the number and diversity of possible permutations for combining C=C π-bond inputs such as alkenes, alkynes, dienes and allenes with polarized π-bond electrophiles such as carbonyls, imines, isocyanates, isocyanides and nitriles. 189,190 The initial reports reviewed here provide key proof-of-principle examples, which demonstrated that this approach can be achieved with high levels of regiocontrol, and when stereocenters are introduced, also diastereocontrol.…”
Section: Three-component Additions To C=c π-Bonds and Polarized πmentioning
confidence: 88%
“…190 Moreover, the reactions proceeded with high diastereoselectivity. Air-stable [Cp*Co(C 6 H 6 )][B(C 6 F 5 ) 4 ] 2 54 in combination with lithium acetate provided the highest yield and diastereoselectivity.…”
Section: Three-component Additions To C=c π-Bonds and Polarized πmentioning
confidence: 96%
“…[5] Despite considerable efforts in this area, most of the protocols developed to date remain limited to two-component reactions.M ulticomponent reactions provide an attractive alternative to streamline the synthesis of complex organic scaffolds. [6,7] Thus,modular three-component carboamination reactions with independent carbon and nitrogen sources are highly desirable. [8] In this regard, Engle and co-workers developed an elegant protocol for the regioselective carboamination of unactivated alkenes involving various nitrogen nucleophiles and carbon Scheme 1.…”
mentioning
confidence: 99%
“…However, among a number of analogous Cp*Co(III) complexes, only [Cp*Co(benzene)](PF 6 ) 2 displayed high efficacy for the addition of 2‐arylpyridines onto multiple bonds in α,β‐unsaturated enones and imines (Scheme a) . Very recently, a remarkable two‐step sequence consisting of cobalt(III)‐catalyzed C–H hydroarylation of α,β‐unsaturated enones and subsequent diastereoselective addition of the cobalt enolate to aldehydes was developed, as was reported by Ellman (Scheme b) . However, the substrate scope of the reaction needs to be further extended.…”
Section: Introductionmentioning
confidence: 99%